Analysis of Technology Fit and User Acceptance in Academic Information Systems Based on E-Learning Using Integrated TTF-TAM Approach in Higher Education - Wahyu Hidayat M; Al Hikma Sake; ST Hutami Haryati M (Jurusan Teknik Informatika dan Komputer, 2025)
This research aims to propose an integrative model that combines the Technology Acceptance Model (TAM), Technology Task Fit Model (TTF), Information System features in state universities, and social motivation to understand the intentions of university students in continuing to use information systems. This research uses cross-sectional research. Cross-sectional is a research to study the dynamics of the correlation between risk factors and effects, using an observational, data collection or approach. With the participation of 70 students, the research results show that the integration of the TAM for adoption and the TTF model for utility provides a comprehensive understanding of behavior, where perceived usefulness and attitudes are crucial in continuance intention. Perceived usefulness is an important mediator of the influence of perceived ease of use, technological task suitability, reputation, social recognition, and social influence on continuance intention. In addition, factors such as perceived ease of use, task-technology fit, reputation, social recognition, and social influence play a significant role in predicting continuance intention. Results showed that personal technology fit, technology-task fit, and openness influenced perceived ease of use. However, perceived ease of use and social influence did not significantly impact attitudes, whereas technology and personal openness did not influence perceived usefulness.